Imidazoline receptors agonists: possible mechanisms of endothelioprotection - Vladislav O. Soldatov; Elena A. Shmykova; Marina A. Pershina; Andrey O. Ksenofontov; Yaroslav M. Zamitsky; Alexandr L. Kulikov; Anna A. Peresypkina; Anton P. Dovgan; Yuliya V. Belousova (Belgorod National Research University, 2018)
Imidazoline receptor agonists are one of the groups of contemporary antihypertensive drugs with the pleiotropic cardiovascular effects. In this review, the historical, physiological, pathophysiological aspects concerning imidazoline receptor agonists and possible mechanisms for their participation in endothelioprotection were considered. Illuminated the molecular biology of each subtype of imidazoline receptors and their significance in the pharmacological correction of cardiovascular disease. IR type 1 are localized in the brain nucleus, carrying out the descending tonic control of sympathetic activation, as well as in the endothelial cells of the vessels and kidneys. Their activation leads to a decrease in blood pressure, slowing the remodeling of the vascular wall and increasing sodium nares. IR type 2 is expressed predominantly in the adrenal gland, fat and muscle tissues. The physiological effects of their stimulation are associated with an increase in glucose utilization by peripheral tissues. IR type 3 are mainly present in pancreatic cells and are associated with the regulation of insulin secretion. Their stimulation leads to an increase in insulin liberation. Thus, IR agonists are able to improve endothelial function through various mechanisms, including blood pressure reduction, improvement in metabolic profile, and direct positive effects on the vascular wall. Current information on the pharmacological effects of this group compounds allows us to conclude that they are a promising group for correcting endothelial dysfunction and complications associated with it.